Geology, geochemistry and Re-Os geochronology of the Jurassic Zeybek volcanogenic massive sulfide deposit (Central Pontides, Turkey) - Gunay, Kurtulus; Donmez, Cahit; Oyan, Vural; Baran, Cuneyt; Ciftci, Emin; Parlak, Osman; Ozkumus, Serkan (Elsevier, 2019)
Located in the north of Anatolia, the Pontide Orogenic Belt hosts Turkey's most important volcanogenic massive sulfide (VMS) deposits. Studies completed in the last ten years have discovered new massive sulfide deposits in the Central Pontide zone. The Zeybek VMS deposit is one of these newly-discovered deposits found in the Central Pontides. This deposit is associated with the Cangaldag Metamorphic Complex occurring as east-west-striking tectonic slices. The Cangaldag Metamorphic Complex is an allochthonous mass of metavolcanic, metavolcanidastic and metaclastic rocks in the form of imbricated tectonic slices. Zeybek massive sulfide deposit is located within metaclastic rocks intercalated with mafic sills or lava flows in this complex. The major ore mineral paragenesis in the Zeybek VMS deposit comprises pyrite, chalcopyrite and sphalerite, with lower amounts of bornite, covelline, chalcocite and magnetite. With thirty thousand meters of drilling in the mineralized area, 20 million ton resources with 0.32 wt% Cu were determined. According to the wall-rock mineralization relationships, mineralization style and ore geochemistry of the Zeybek VMS mineralization, it is similar to a mafic-siliciclastic type volcanogenic massive sulfide formation. Re-Os geochronologic studies of chalcopyrites from the Cu-rich massive ore samples obtained a 178 +/- 2.2 Ma (MSWD: 4.1) Re-187/Os-188 against Os-187/Os-188 isochron. Geochemical and isotopical age data associated with the Zeybek VMS deposit indicate that the mineralization occurred in an arc-back arc tectonic environment, which developed in Middle Jurassic age intra-ocean as a result of the closure of north-ward subduction that resulted the closure of the Tethys ocean.
Keywords: Central Pontide; Mafic-silisiclastic; VMS; Besshi; Re-Os geochronology